Financing of Dividend Payouts on The Example of Commodity Companies in Poland - Konrad SZYDLOWSKI (Communications of International Proceedings, 2022)
The article raises the issue of financing dividend payouts. The research goal was to identify companies’ financial needs connected with the dividend policy and sources of financing dividend payouts. The research covered companies listed in the Warsaw Stock Exchange. The research sample consisted of enterprises related to the commodity market. They represented the energy, mining, fuel, chemical and construction sectors. The research results indicated the good financial condition of the analyzed enterprises. These were profitable companies with low indebtedness and adequate financial liquidity. The analyzed companies differed in the amounts and regularity of dividend payouts. Some companies paid dividends regularly while others did it sporadically. In most cases, dividend payments were covered by net profit and cash from operating activities. Situations in which companies needed to introduce complementary sources of financing were marginal. This confirms the conservative and well-balanced strategies of financing dividend payouts.
Keywords: dividend policy; sources of financing.